Liberia : Joint Staff Advisory Note on the First Annual Progress Report on the Implementation of the Liberia Poverty Reduction Strategy (LPRS). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Annual Progress Report (APR) provides no estimates or analysis of current poverty levels and the poverty effects of the Liberia Poverty Reduction Strategy (LPRS) in the absence of reliable statistics. IMF staff recommends including a thorough poverty diagnosis that builds on the results of the two Core Welfare Indicator Questionnaires (CWIQs) in the next APR. During the first year of implementation of the LPRS, the authorities have strengthened the environment for sustainable economic growth, development, and poverty reduction. Progress in reforming and activating the productive sectors-particularly forestry, mining, and agriculture-has been slower than expected.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet